Predators with pouches : the biology of carnivorous marsupials - Jones, Menna (CSIRO, 2003)
Predators with Pouches provides a unique synthesis of current knowledge of the worlds carnivorous marsupials from Patagonia to New Guinea and North America to Tasmania. Written by 63 experts in each field, the book covers a comprehensive range of disciplines including evolution and systematics, reproductive biology, physiology, ecology, behavior, and conservation.